Online medical knowledge FAQ database / Er Hock Chiye - Er , Hock Chiye (2003)
Online Medical Knowledge FAQ Database is a web-based application system that provides frequently asked questions about health and medical knowledge for the public. Search function will be provided in the system as well as interaction between the users and medical consultants. The objectives of this system are to provide the public with an easily accessible online reference resource about common medical knowledge, to create public awareness in the matters of health and to distribute medical knowledge that caters for all levels of Malaysian society. The main system divided into six modules which are Registration Module, User Group Module, Administrator and Moderator's Module, Search Module, Help Module and Feedback Module, Waterfall Model is the methodology that is being applied by developer in developing the project After doing a thorough literature review, the project developer has decided to choose Hypertext Preprocessor (PHP) as the server-side scripting language. The combination of PHP, MySQL and Apache will be set up as the back-end software technology of the system. The system will be developed on the Windows NT environment. Other related software and development tools such as Internet Explorer 5, Adobe Photoshop 6 and Macromedia Dreamweaver 4 will also be used to develop the system.